Role of Forests in Rural Economy of Himachal Pradesh - Singh, D. V. (Indian Forester, 1995)
The present study is designed to know the extent of forest resources and economic returns to the rural people of Himachal Pradesh and is based on field data collected under wood balance study of A.E.Rr Centre, H.P. University, Shimla from 560 respondents of different size classes spread in four agro-climatic zones of the State. The study aims at' not only estimating the extent of dependence of locals upon forests, but also at providing a value (in monetary terms) to the usufructs availed by the villagers from the forests in the State. The sampling design of study is based on multistage stratified random sampling. The data pertains to 365 days for the year 1989-90 and was collected by day to day accounting.